Hemiballismus and Normal Pressure Hydrocephalus as Long-Term Sequelae following a Hemispherectomy for Intractable Epilepsy in a Man with a Learning Disability - Joseph Joyce; Shoumitro Deb (Behavioural Neurology)
We report here a case of a 48-year-old gentleman with mild/moderate learning disability who developed late complications of hemispherectomy 28 years following the operation. The original operation was performed to treat intractable epilepsy (both generalized tonic/clonic and complex partial seizures) in an 8-year-old boy. After a 28 year seizure-free period, the patient developed cognitive decline, seizures, hemiballismus and a subacute confusional state, possibly related to normal pressure hydrocephalus. A ventriculo-peritoneal shunt operation, along with treatment with high doses of sulpiride, brought improvement in both mental state and hemiballismus.